Hyperglycemia amplifies TLR-mediated inflammatory response of M(IL4) macrophages to dyslipidemic ligands - Badillo-Garcia, Luis Ernesto; Liu, Quan; Ziebner, Kim; Balduff, Michael; Sevastyanova, Tatyana; Schmuttermaier, Christina; Klüter, Harald; Harmsen, Martin; Kzhyshkowska, Julia (Journal of leukocyte biology, 2024)
Hyperglycemia is critical for initiation of diabetic vascular complications. We systemically addressed the role of hyperglycemia in the regulation of TLRs in primary human macrophages. Expression of TLRs (1-9) was examined in monocyte-derived M(NC), M(IFNγ), and M(IL4) differentiated in normoglycemic and hyperglycemic conditions. Hyperglycemia increased expression of TLR1 and TLR8 in M(NC), TLR2 and TLR6 in M(IFNγ), and TLR4 and TLR5 in M(IL4). The strongest effect of hyperglycemia in M(IL4) was the upregulation of the TLR4 gene and protein expression. Hyperglycemia amplified TLR4-mediated response of M(IL4) to lipopolysaccharide by significantly enhancing IL1β and modestly suppressing IL10 production. In M(IL4), hyperglycemia in combination with synthetic triacylated lipopeptide (TLR1/TLR2 ligand) amplified expression of TLR4 and production of IL1β. In summary, hyperglycemia enhanced the inflammatory potential of homeostatic, inflammatory, and healing macrophages by increasing specific profiles of TLRs. In combination with dyslipidemic ligands, hyperglycemia can stimulate a low-grade inflammatory program in healing macrophages supporting vascular diabetic complications.